Hydraulic computations for flood routing of a modular urban stormwater drainage system - Cruz, Eric C.
This paper discusses the hydraulic analyses carried out to evaluate flooding due to overbanking of stretches of a 4 meter wide drainage canal through an existing subdivision in Metro Manila. The proposed land development will convert the upstream portion of the property into a mixed use commercial residential area. Computations are carried out to determine the spatial extent of the present flooding potential, and to quantify the upstream migrated inundated areas under the present condition of a submerged exit. Hydraulic analyses are also undertaken to solve the recurring problem of a submerged culvert outfall. The study also provides the quantitative bases for the structural measures to mitigate the flooding hazards associated with the land use modifications. It is concluded that hydraulic computations are necessary in predicting local flooding conditions, as well as in analyzing the effects of proposed engineering interventions to mitigate this condition. The methodology is demonstrated via project application involving an urban stormwater drainage system.
Keywords: Flood routing; Urban drainage; Stormwater; Hydraulic analysis